1985
DOI: 10.1073/pnas.82.21.7165
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Yb-glutathione-S-transferase as a major rat liver protein labeled with dexamethasone 21-methanesulfonate.

Abstract: (6). This steroid derivative also acts as a long-term irreversible anti-glucocorticoid in HTC cells (1-3). The covalently bound steroid-receptor complexes are activated to DNA binding forms (6-8) and then bind to the same long-terminal-repeat regions of mouse mammary tumor virus DNA (9) as the noncovalent complexes.Glutathione S-transferases (glutathione transferase, EC 2.5.1.18) are a family of enzymes that catalyze reactions of glutathione (GSH) with compounds that contain electrophilic centers. Through this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Mammal GSTs have the ability to bind hormones and particularly sexual steroids, to influence their transport, metabolism, and action (13,16). Direct binding of testosterone for mammal GST with moderate affinity (10 (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammal GSTs have the ability to bind hormones and particularly sexual steroids, to influence their transport, metabolism, and action (13,16). Direct binding of testosterone for mammal GST with moderate affinity (10 (16).…”
Section: Discussionmentioning
confidence: 99%
“…Mammal GSTs are also involved in the intracellular transport of a variety of endogenous metabolites, drugs, and hormones by their abilities to bind these substances (16). Particularly, GSTs are glucocorticoid-binding proteins and, thereby, may influence transport, metabolism, and action of steroids (13). It has also been demonstrated that testosterone and progesterone have the ability to bind mammal GSTs with moderate (10…”
mentioning
confidence: 99%
“…The GST family of enzymes, and in particular the GST-P1 isoform, is localized mainly in the cytotrophoblast at all stages of pregnancy, and its expression increases WT Wild type with development [51]. These enzymes bind various ligands such as steroids [20][21][22] and may play a role in the clinical response to GCs in acute lymphoblastic leukemia [25,52]. Phenotypically relevant genetic polymorphisms have been identified also in some human cytosolic GST isoenzymes, and in particular, in families M1, P1, and T1.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes have previously been shown to bind to GCs and to play a role in the metabolism and response to these hormones [20][21][22][23]. Phenotypically relevant genetic polymorphisms for some GST subclasses (GST-M1, GST-T1, and GST-P1) have been related to the outcome of several diseases, including acute lymphoblastic leukemia and solid tumors [24], and to response to GCs [25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the transferases bind a number of hydrophobic compounds such as heme, bilirubin and dexamethasone. Their expression can be induced by various xenobiotics such as transstilbene oxide [9,10] and for many toxic xenobioties, glutathione S-conjugate formation represents a detoxication pathway [7,8]. The GSTs are either homodimers or heterodimers composed of at least eight subunits (Ya, Yb1, Yb2, Yb3, Yc, Yk, Yn and Yp) which are expressed tissue-specifically and can be distinguished according to their substrate specificity.…”
Section: Introductionmentioning
confidence: 99%